Degradable collagen/sodium alginate/polyvinyl butyral high barrier coating with water/oil-resistant in a facile and effective approach. (15th February 2022) - Jing, Xin; Li, Xia; Jiang, Yifei; Lou, Jiang; Liu, Zhuqing; Ding, Qijun; Han, Wenjia
Abstract: Degradable bio-based materials have been widely considered as functional coatings, however, it is a great challenge to fabricate biodegradable coatings with high barrier, water- and oil- resistance. In this work, such coatings were fabricated by using collagen fibers (CF), sodium alginate (SA), and polyvinyl butyral (PVB). CF and SA were mixed evenly and coated on Ca 2+ pretreated filter paper. It was mainly due to the electrostatic adsorption between collagen fibers and sodium alginate, and the crosslinking between the adsorption products and Ca 2+ . By coating PVB solution, the barrier performance was further improved. Notably, the composite exhibited excellent water vapor resistance (48 g/m 2 ·24 h), water resistance (31 g/m 2 ), oil resistance (kit rating: 12/12) and good mechanical properties. This degradable, environmentally friendly, and simple composite paper method has excellent barrier properties, mechanical properties and fluorine-free properties, and will have many applications in the food and packaging fields. Graphical abstract: The electrostatic adsorption between collagen fibers and sodium alginate and the cross-linking reaction between sodium alginate and Ca 2+ are combined with paper-based materials in a simple process, and a layer of PVB is simply coated. The water resistance, oil resistance, and water vapor barrier properties of paper have been significantly improved, and there will be many applications in the real food and packaging fields. Unlabelled Image